PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN PEMERKOSAAN (ANALISIS DAMPAK PSIKOLOGIS TERHADAP PUTUSAN MAHKAMAH SYAR’IYYAH KOTA LANGSA) - Amrunsyah (IAIN Langsa, 2018)
The implementation of legal protection for child victims of rape has not been maximized as provided by the Law. Even though it has not been maximal, there are several forms of legal protection that have been given to children as victims according to Law Number 35 Year 2014 concerning Child Protection article 64 paragraph (3), that children as victims get (a) rehabilitation both within institutions and outside the institution , (b) identity protection and reporting efforts through the mass media to avoid labeling, (c) providing safety guarantees for witnesses of victims and expert witnesses both physically, mentally and socially, and (d) providing accessibility to obtain information about the development of cases. first, getting harmony between the theories used with legal decisions carried out by the Langsa City Islamic Court. Second, knowing the psychological impact of child rape victims and thirdly, the obstacles faced in deciding the rape of the rape are still different from the Law on Child Protection, meaning that there is still dualism in the laws that apply in Aceh, including in Langsa City.